Application of objective physical activity measurement in an antenatal physical activity consultation intervention: a randomised controlled trial. (December 2015) - Currie, Sinead; Sinclair, Marlene; Liddle, Dianne; Nevill, Alan; Murphy, Marie
Abstract Background Physical Activity (PA) during pregnancy has many health benefits, however, inactivity in this population is common and PA often declines with increasing gestation. PA consultations have been useful in promoting PA in the general population, however their use for addressing PA in pregnancy is unknown. This study aimed to examine if a theory-based intervention using PA consultations would reduce the magnitude of decline in objectively measured PA between the first and third trimesters of pregnancy. Methods A RCT was carried out in an urban maternity unit in Northern Ireland between September 2012 and June 2013. 109 low-risk, primigravida pregnant women were randomised to a control (n  = 54) or intervention group (n  = 55). Intervention participants received three face-to-face individual PA consultations. Daily PA was measured in each trimester using seven day accelerometry. The study was approved by a NHS trust (12/NI/0036). PA data in counts per minute (CPM) were categorised into intensity using Freedson cut points and mean minutes of PA were compared between groups using repeated measures ANOVA with a sub-analysis stratifying participants per PA level in trimester one. Results Intention to treat analysis was performed on data from 97 participants. Time in moderate, vigorous and moderate-vigorous intensity PA (MVPA) significantly declined between trimesters one and three in both groups (P  < 0.001). There were no statistically significant differences in PA between groups in any trimester. Women in the intervention group who were less active in trimester one did not demonstrate a significant decline in MVPA throughout pregnancy (in contrast with the decline identified in the more active participants). Conclusions The findings indicate that PA consultations were not effective in reducing the decline of MVPA in throughout pregnancy, however, women who were less active in trimester one and received PA consultations had a lesser decrease in MVPA. It is possible that pregnant women, specifically those who are more active at the start of pregnancy, have differing needs for PA behaviour change and maintenance, requiring more intense interventions than less active women. Trial Registration Current Controlled Trials RegisterISRCTN61829137 .